The Nlrp3 inflammasome - the evolving story of its positive and negative effects on hematopoiesis - Ratajczak, Mariusz Z. (Curr Opin Hematol, 2021)
PURPOSE OF REVIEW: Hematopoiesis is co-regulated by innate immunity, which is an ancient evolutionary defense mechanism also involved in the development and regeneration of damaged tissues. This review seeks to shed more light on the workings of the Nlrp3 inflammasome, which is an intracellular innate immunity pattern recognition receptor (PRR) and sensor of changes in the hematopoietic microenvironment, and focus on its role in hematopoeisis. RECENT FINDINGS: Hematopoietic stem progenitor cells (HSPCs) are exposed to several external mediators of innate immunity. Moreover, since hemato/lymphopoietic cells develop from a common stem cell, their behavior and fate are coregulated by intracellular innate immunity pathways. Therefore, the Nlrp3 inflammasome is functional both in immune cells and in HSPCs and affects hematopoiesis in either a positive or negative way, depending on its activity level. Specifically, while a physiological level of activation regulates the trafficking of HSPCs and most likely maintains their pool in the bone marrow, hyperactivation may lead to irreversible cell damage by pyroptosis and HSPC senescence and contribute to the origination of myelodysplasia and hematopoietic malignancies. SUMMARY: Modulation of the level of Nrp3 inflammasome activation will enable improvements in HSPC mobilization, homing, and engraftment strategies. It may also control pathological activation of this protein complex during HSPC senescence, GvHD, the induction of cytokine storms, and the development of hematopoietic malignancies.